Texts in context : essays on dating and contextualising Christian writings from the second and early third centuries - Nicklas, Tobias, 1967-; Schröter, Jens, 1961-; Verheyden, Joseph, 1957- (Bibliotheca Ephemeridum theologicarum Lovaniensium, 2021)
"The essays collected in this volume contain the proceedings of a colloquium held in Leuven in December 2018. The overall purpose was to study Gnostic and other second- and early third-century Christian texts in search for indications and criteria for determining their place in the development of early Christian theology. A good deal of attention is given to dating and identifying these often anonymous writings, but other aspects are also addressed. The essays illustrate in various ways that this development was not a uniform process. The many problems involved in studying these texts from such a perspective have brought some scholars to question what should be the main focus: the (presumed) original context or their transmission and use by later generations. The collection includes essays by P. Foster (Ignatius), C.M. Tuckett (1-2 Clement), J.S. Kloppenborg (the Didache and the Apostolic Constitutions), J. Frey (Jewish-Christian gospels, especially the Gospel according to the Hebrews), H. Lundhaug (methodology in studying Gnostic texts), C. Jacobi (Gospel of Philip), K. Schwarz (Gospel of Thomas), F. Watson (Apocryphon of James), J.-D. Dubois (criteria for dating Gnostic texts, applied to the Apocryphon of John), D.M. Burns (Nag Hammadi tractates with philosophical interests), and A. Van den Kerchove (Gospel of Judas)."